The Influence Of Incipient Ability, Indpendent Learning To Critical Thinking Ability Through Teaching Material Inquiry-Based - Rajagukguk, Waminton (Advances in Social Sciences Research Journal, 2017)
To foster mathematical teaching material inquiry based aided by multimedia that caused to upgrade critical thinking of High School Students (HSS) across North Sumatera as the focused purpose of this study. Implemented in North Sumatera from the year of 2016 to 2018. The population covered overall high school students. The subjects were the high school students themselves. Technically picking sample on by exercising purposive random sampling that is pick on six HSS randomly with three HSS from public school and three HSS from private school. To perceive the influence of teaching material of mathematics inquiry-based aided by multimedia which is developed used designed research of quasi experiment with design control group post test only. Technically to turn in data used questionnaires, observation, and test. The data being analyzed with working out with technical descriptive analysis, examined t and anova. The experiment of study found inquiry learning model in groups caused students are encouraged to express their thoughts and keeping others thoughts. Inquiry learning model aided by multimedia interacts with students’ incipient mathematical ability to critical thinking ability. Students’ incipient mathematical ability in low and high category rather used inquiry learning aided by multimedia, meanwhile for students’ incipient ability of low rather used ordinary learning model or expository. Students critical thinking are more in medium category that is of 38.71%, this case means that to upgrade critical thinking ability in this study its necessary to focus on one of the third limitedness in allowing more opportunities to students to think creatively.